Islamic Banking Efficiency in The Covid-19 Pandemic Era and The Role of Digitalization - Ihsanul Ikhwan; Aam (Ekonomi Islam Indonesia, 2022)
Over the past two years, the COVID-19 pandemic has affected the banking industry. In the current sustainable era, increasing efficiency is one of the goals that must be achieved by banks. This study aims to measure the efficiency of Islamic banking, especially during the COVID-19 pandemic from 14 Islamic banks in Indonesia within a period of 6 years, from 2015 to 2020. The non-parametric method, Data Envelopment Analysis (DEA) is used as a research method in measure efficiency. DEA results are also used to identify input and output variables that must be improved if a decision-making unit (DMU) needs to increase its efficiency in the form of potential improvement. The results of the study show that COVID-19 has an impact on decreasing the efficiency of Islamic banking in Indonesia. The Islamic banks with the highest efficiency scores are Bank Syariah Mandiri, BRI Syariah, and Maybank Syariah. Furthermore, based on the analysis of potential improvement, the most important variable to be improved by banks during the pandemic is the variable amount of financing. Islamic banking is also required to be able to adapt to digitalization in order to survive during the crisis caused by the COVID-19 pandemic and remain able to compete with conventional banking or new startups in the banking sector.